Selection of Strategic Pathways for the Comprehensive Development of Peru through the Analytical Hierarchy Process (AHP) - Hugo Flor-Cunza; Jandra Rojas Chavez; Antony De la Cruz-Vasquez; Pedro Sanchez-Huapaya; Linett Velasquez-Jimenez (Journal of Applied Engineering and Technological Science (JAETS), 2026)
This study prioritizes strategic pathways for Peru’s comprehensive development using the Analytic Hierarchy Process (AHP). It addresses a methodological gap in development planning research by applying a unified multicriteria framework to compare heterogeneous national policy pathways that are often assessed separately. Four alternatives were evaluated: science and technology, tourism, infrastructure, and anemia reduction. The decision model included four criteria—economic impact, social impact, sustainability, and feasibility—based on pairwise judgments from a multidisciplinary panel of four experts in economics, civil engineering, public health, and sustainable tourism. The results showed that economic impact was the dominant criterion (0.518), followed by social impact (0.255), feasibility (0.169), and sustainability (0.057). The criteria matrix achieved acceptable consistency (CR = 0.047). After aggregating local and global priorities, science and technology ranked first (0.366; 36.6%), followed by tourism (0.270; 27.0%), infrastructure (0.243; 24.3%), and anemia reduction (0.122; 12.2%). A sensitivity analysis showed that the ranking remained stable under moderate variations in criterion weights. The study provides a transparent and replicable AHP-based framework for intersectoral prioritization and a practical analytical tool for development policy discussion in Peru.